Improving Students’ Critical Thinking Skills Through the Development of E-Learning-Based Chemistry Textbooks - Wahyudiati, Dwi; Qurniati, Devi (Journal of Research in Mathematics, Science, and Technology Education, 2025)
This study was conducted with the aim of developing an effective and feasible e-learning-based chemistry textbook intended to enhance students’ critical thinking abilities. The development process adhered to the ADDIE model, providing a systematic framework for the design of educational materials. Participants in the study consisted of first-semester chemistry education students at the Faculty of Tarbiyah and Teacher Training, UIN Mataram. Data were collected using both test and non-test instruments. Non-test instruments were employed to evaluate the feasibility of the e-learning-based chemistry textbook, whereas test instruments were used to measure students’ critical thinking skills. The study was carried out in two primary stages: validation of the product and trials involving chemistry education students at UIN Mataram. For the trials, a quasi-experimental design with a pre-test/post-test control group was implemented. The results of the study led to the following conclusions: (1) The developed e-learning chemistry textbook attained validity scores ranging from 0.857 to 0.905, classifying it as very high, with a reliability coefficient of 0.865. These results indicate that the textbook is valid and reliable for use in Basic Chemistry courses at the tertiary level. (2) Analysis using an independent samples t-test revealed a significance value of 0.018, below the alpha threshold of 0.05, confirming that the e-learning chemistry textbook is effective in improving students’ critical thinking skills. Overall, the findings demonstrate that the developed e-learning-based chemistry textbook is both valid and reliable, and it effectively enhances students’ critical thinking abilities.